Optimization of Lip Balm Formulation of Cucumber Fruit Extract (Cucumic Sativus L.) - Sulistyianingsih; Ika Buana januarti; Badrus Sholeh; Lisa Listia Ningrum; Khaila Khairunnisa (Universitas Ngudi Waluyo, 2025)
Cucumber is one of the herbal plants that contains antioxidants, vitamins, and minerals that are used to overcome skin problems, so it is suitable for use in making lip balm. The purpose of this study was to obtain the results of optimization of the formulation and physical evaluation of the preparation of cucumber fruit extract lip balm (cucumic sativus l.) that meets the requirements. This type of research is experimental, with the Simplex Lattice Design approach. Then the physical evaluation test of the preparation was carried out including organoleptic, homogeneity, pH, adhesive power, and melting point. The results of the organoleptic test were bone white, peppermint oil odor, and semi-solid texture. The homogeneity test showed that there were no coarse grains. The pH test obtained results according to the requirements of 4.5 - 8. The adhesion test obtained results according to the requirements >4 seconds. And in the melting point test the results were according to the requirements of 50 -70 0 C. Analysis of SPSS 25 results using one sample t-test, obtained pH test results of 0.076, adhesion test of 0.627, and melting point test of 0.410, thus showing a value (p>0.05) which means there is no significant difference between the predicted value and the experimental results.